INVESTIGATION OF HABITABILITY INDICES OF YTU GULET SERIES IN VARIOUS SEA STATES - Cakici, Ferdi; Aydin, Muhsin (BRODARSKI INST, 2014)
This paper presents habitability indices of gulet-type boats for the vertical plane motions in specified sea states. Gulets are commonly used in the Mediterranean and the Aegean Sea as pleasure boats. Therefore, it is very important to obtain their habitability indices. Thus, 21 different gulet forms developed as a result of iterative studies are used for analyses. The ISO 2631 standard that defines the effect of different levels of vertical accelerations on humans is used as the first seakeeping criterion. Other seakeeping criteria are obtained from NATO Standardization Agreement (STANAG) documents for pitch motion. Seakeeping analyses are carried out by using commercial software which is based on the strip theory and statistical short term response prediction method. The effect of displacement forces, selected criteria and sea conditions on habitability indices is presented.
Keywords: motion on vertical planes; habitability; seakeeping criteria; strip theory; CRITERIA; Engineering